2023
DOI: 10.3390/insects14010066
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methyl Bromide and Ethyl Formate for Fumigation of Snail and Fly Pests of Imported Orchids

Abstract: Invasive snails and flies are major pests of imported orchids, controlled by methyl bromide (MB) fumigation in Korea. We compared the efficacy and phytotoxicity of ethyl formate (EF) and MB on four species of imported orchids using juvenile stages of Achatina fulica and third and fourth instars of Lycoriella mali. EF was as effective as MB. The LCt99 values of EF were 68.1 and 73.1 g h/m3 at 15 °C; and those of MB were 95.9 and 78.4 g h/m3 at 15 °C for A. fulica and L. mali, respectively. In the scale-up trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The potential harm to plants from EF has been previously assessed across a range of plants grown in nurseries [ 20 , 25 ], as well as in fruits [ 21 , 26 , 37 , 38 ] and vegetables [ 39 ]. These studies indicated that the extent of the harmful effect depended on factors such as the treatment amount used and the plant species and variety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The potential harm to plants from EF has been previously assessed across a range of plants grown in nurseries [ 20 , 25 ], as well as in fruits [ 21 , 26 , 37 , 38 ] and vegetables [ 39 ]. These studies indicated that the extent of the harmful effect depended on factors such as the treatment amount used and the plant species and variety.…”
Section: Discussionmentioning
confidence: 99%
“…When applied to fruits such as oranges, bananas, grapes, and persimmons, EF demonstrated no negative impact on overall fruit quality [ 21 , 26 , 37 , 38 ]. In nursery plants, the observed levels of EF-induced plant damage varied, ranging from absence of harm (for instance, in Ficus benghalensis Banyan and Cymbidium goeringii Reichenbach) to significant harm (as observed in Anthurium andraeanum Linden and Agave attenuata Salm-Dyck) [ 20 , 25 ]. In this study, there were no significant changes in fruit firmness, sugar content, color change, and weight loss 1 week after the EF treatment at 5 or 10 g/m 3 at 5 ± 1 °C ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cho et al (2020) show that fumigation with ethyl formate mixtures with a concentration of 16 mg/L and PH 3 0.1 mg/L for 4 hours, can ensure the complete death of imago and nymphs of these pests. However, Kwon et al (2023) focus on the fact that the phytotoxic effect of the examined gas mixtures on live plants was considerably lower, in contrast to brommethyl.…”
Section: Introductionmentioning
confidence: 99%